Strategic thinking: tools of competition for the new millennium management guidance (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2010)
The purpose of strategic thinking to help organizations in the exploration of future challenges, both predictable and unpredictable, rather than prepare them for possible only tomorrow. From there, the research developed, is an essay on the role of strategic thinking as a tool of competitiveness-oriented management of the new millennium, considering the theoretical basis of experts and Omaha (2004), Morrisey (2006), Porter (1999), among others. In this sense it is, that the methodology used for the study was descriptive and documentary, considering the hermeneutic for content analysis. Results demonstrate the competitive dynamics of organizations and markets manifest conduct under which they are best suited to the environment will be those that will endure. This is because, among other things, that are better equipped and prepared to face an environment of constant change and uncertainty. Characterized it, by reducing the life cycles of products, permanent changes in the needs and tastes of consumers, as well as the quality and timeliness of information available.
Keywords: thinking; strategic thinking; competitiveness